Prefrontal cortex activity is reduced in gambling and nongambling substance users during decision-making - Tanabe, Jody; Thompson, Laetitia; Claus, Eric; Dalwani, Manish; Hutchison, Kent; Banich, Marie T. (Human brain mapping, 2007)
Objective: Poor decision‐making is a hallmark of addiction, whether to substances or activities. Performance on a widely used test of decision‐making, the Iowa Gambling Task (IGT), can discriminate controls from persons with ventral medial frontal lesions, substance‐dependence, and pathological gambling. Positron emission tomography (PET) studies indicate that substance‐dependent individuals show altered prefrontal activity on the task. Here we adapted the IGT to an fMRI setting to test the hypothesis that defects in ventral medial and prefrontal processing are associated with impaired decisions that involve risk but may differ depending on whether substance dependence is comorbid with gambling problems. Method: 18 controls, 14 substance‐dependent individuals (SD), and 16 SD with gambling problems (SDPG) underwent fMRI while performing a modified version of the IGT. Result: Group differences were observed in ventral medial frontal, right frontopolar, and superior frontal cortex during decision‐making. Controls showed the greatest activity, followed by SDPG, followed by SD. Conclusion: Our results support a hypothesis that defects in ventral medial frontal processing lead to impaired decisions that involve risk. Reductions in right prefrontal activity during decision‐making appear to be modulated by the presence of gambling problems and may reflect impaired working memory, stimulus reward valuation, or cue reactivity in substance‐dependent individuals. Hum Brain Mapp, 2007. © 2007 Wiley‐Liss, Inc.